Trajetória de formação pessoal e profissional: entre saberes, experiências e narrativas - Souza, Francisco Rodrigues de (Brasil, 2024)
I present in this TCC (Course Completion Work) a description of the most relevant aspects of my academic trajectory, from the Basic Education phase to my Graduation in Pedagogy. In this description, I particularly address the three dimensions to which I dedicated myself throughout my professional career: Research, Teaching, and Extension. The greatest emphasis in this Memorial is given to describing my involvement in a sequence of Research Initiation, both as a teacher of Early Childhood Education and Elementary School I. I aimed to describe – with a certain degree of detail – the sequence of teaching actions in which I was involved, which, in my understanding, became both the foundation and the guiding principle for the development of this work, but which also ended up being part of my future plans. Consequently, I present this TCC as previously mentioned. Following the Memorial, I also documented my extensive experience in teaching activities, spanning Early Childhood Education and Elementary School I, which has provided me with both theoretical and practical knowledge to work confidently and professionally in the educational field.